2014
DOI: 10.3109/09637486.2014.937797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dried pomegranate (Punica granatum) peel powder (DPPP) on textural, organoleptic and nutritional characteristics of biscuits

Abstract: Pomegranate (Punica granatum) peel is rich source of dietary fiber and bioactive compounds, hence could be used in the development of functional food formulations. Attempt was made to see the effect of dried pomegranate peel powder (DPPP) and emulsifiers on the rheological, nutritional and quality characteristics of biscuits. Incorporation of DPPP from 0 to 10% increased farinograph water absorption, decreased dough stability, increased amylograph pasting temperature and peak viscosity of wheat flour; increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
8
25
1
3
Order By: Relevance
“…Hayta, Özuğur, Etgü, and Şeker (2014) attributed this result to the high water absorption capacity of the fiber causing an increase in the hardness values of biscuits. Srivastava, Indrani, and Singh (2014) and Awolu, Sudha, and Manohar (2018) also found similar results for the effect of dried pomegranate peel powder and mango kernel seed on textural properties of biscuits, respectively.…”
Section: Resultsmentioning
confidence: 57%
“…Hayta, Özuğur, Etgü, and Şeker (2014) attributed this result to the high water absorption capacity of the fiber causing an increase in the hardness values of biscuits. Srivastava, Indrani, and Singh (2014) and Awolu, Sudha, and Manohar (2018) also found similar results for the effect of dried pomegranate peel powder and mango kernel seed on textural properties of biscuits, respectively.…”
Section: Resultsmentioning
confidence: 57%
“…Studies about the incorporation of fruit by-products in cookies include the addition of apple pomace (Coehlo and Wosiacki, 2010;Kohajdova et al, 2014;Sudha et al, 2016), berry pomace (Saric et al, 2016;Tanska et al, 2016), sour cherry pomace (Saponjac et al, 2016), mango peel (Ajila et al, 2008), banana peel (Arun et al, 2015b), green banana flour (Agama-Acevedo et al, 2012), pumpkin and carrot pomace (Turksoy and Ozkaya, 2011), pomegranate peel (Srivastava et al, 2014), citrus peel powder (Younis et al, 2016), grapefruit and citrus fiber (Kohajdova et al, 2011(Kohajdova et al, , 2013, potato peel (Arora and Camire, 1994) and watermelon rind (Naknaen et al, 2016). In Table 2, a partial listing of papers on practical uses of FVB on cookies is shown.…”
Section: Cookiesmentioning
confidence: 99%
“…Studies have shown that the incorporation of FVB reduced the expansion of the dough during baking, resulting in cookies with smaller diameter and higher hardness. The expansion of doughs during baking is reduced when flours have high water absorption capacity (Pareyt and Delcour, 2008), which is a physical parameter that is increased in the presence of fiber (Collar et al, 2006) and flour/by-product mixtures (Ajila et al, 2008;Kohajdova et al, 2011Kohajdova et al, , 2013Kohajdova et al, , 2014Turksoy and Ozkaya, 2011;Srivastava et al, 2014;Naknaen et al, 2016). Although it was not analyzed with the incorporation of FVB, doughs made with mixtures with higher water absorption capacity yielded higher consistency (Mancebo et al, 2016), resulting in problems during sheeting.…”
Section: Physical and Sensory Quality Of Cookies As Affected By Fvbmentioning
confidence: 99%
“…; Srivastava et al . ). Interestingly, no observed adverse effect levels of PoPx have been claimed as >2,000 mg/kg b.w.…”
Section: Introductionmentioning
confidence: 97%
“…Abundant literature is available to demonstrate antioxidant and antimicrobial properties of PoP and its extracts and their utilization as supplements in chicken meat and its products (Kanatt et al 2010;Devatkal et al 2013), white shrimps (Basiri et al 2015), goat and chicken meat patties (Naveena et al 2008;Devatkal et al 2010), sunflower oil (Iqbal et al 2008), cookies (Ismail et al 2014), panbread (Sayed-Ahmed 2014), paneer (Singh and Immanuel 2014) and apple juice (Altunkaya et al 2013). Several groups of researchers elucidated pomegranate bagasse, to act as potential source of dietary fibers, minerals and natural colorants that could complement functional, structural and textural properties to cereal based preparations (Viuda-Martos et al 2012;Ismail et al 2014;Srivastava et al 2014). Interestingly, no observed adverse effect levels of PoPx have been claimed as >2,000 mg/kg b.w.…”
Section: Introductionmentioning
confidence: 99%